EFFECT OF MELATONIN SUPPLEMENTATION AND TYPE 2 DIABETES MELLITUS (T2DM) : A SYSTEMATIC REVIEW - Derrick,; Halim, Hendry (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2022)
Pineal gland secretion of the endogenous indole amine known as melatonin is regulated by the hypothalamus. The 24-hour cycle of circadian rhythms is partially responsible for the timing of physiologic processes. Research conducted in the past has demonstrated that melatonin possesses a variety of advantageous properties, such as activities that limit the responses of adrenocorticotropic hormones and good effects that have an effect on metabolic profiles. In addition, there has been research carried out on animals, in addition to certain human trials that were not randomized, which have suggested that the use of melatonin may have a positive influence on improving glycemic control, insulin resistance, hypertension, and dyslipidemia. These studies were carried out in conjunction with one another. In studies conducted on both humans and animals, melatonin was discovered to have a beneficial effect on the regulation of blood glucose levels. The expression of the glucose transporter type 4 (GLUT4) gene is reduced in mice that have had their pineal glands surgically removed, which leads to glucose intolerance and insulin resistance. Melatonin treatment is effective in reducing the severity of these symptoms. Melatonin's anti-oxidative activity effectively lowers oxidative stress, which is a significant contributor to the progression of a wide variety of problems that can arise from diseases such as diabetes.